Games to create awareness and design policies for transboundary cooperation in river basins: lessons from the Shariva Game of the Mekong River Commission - Douven, W.; Mul, Marloes L.; Son, L.; Bakker, Nico; Radosevich, G.; Hendriks, A. (Springer, 2014)
International river basins cover a vast majority of the land surface, international cooperation is therefore important for the proper management, and to assure equitable and effective use in the basins. Key elements to improve international cooperation are common understanding of the issues in the basin, understanding upstream-downstream impacts and sharing a common vision for the future. This article focuses on the role of games in international basin cooperation to create awareness and to support policy development. The paper analysed the effects of the game in creating awareness and upgrading knowledge amongst water and related professionals and in designing procedures for cooperation in transboundary river basins. This was analysed during the implementation of the game with 28 participants from the four Lower Mekong countries. The impact on creating awareness and upgrading knowledge was evaluated through the use of questionnaires and pre- and post evaluation questions and for the design of policies, a SWOT analysis was used to evaluate the usefulness of the policies and frameworks as well as to identify possible improvements to the framework. The game implementation proved to be an appropriate tool to provide a practical way for stakeholders to become acquainted with the administrative and technical tools available in the Lower Mekong Basin. Pre- and post test shows that participants gained substantial knowledge on transboundary cooperation and use of tools. The game was part of a longer training programme addressing all the issues, however, the participants gained additional knowledge and insight by playing the game, well above what they had learned during the earlier training workshops. Playing the game proved an important aspect in training and education of such complex systems. The study also shows the role games can play in policy analysis, in particular the way the game provided insight in the design of the policy and the development of procedures, and their function to review and update policies and procedures. A number of recommendations have been made to strengthen the role in both training and education as well as in design of procedures.